Gesture recognition system for deaf and dumb - FarooqHussain, Dr.; Gandhi, Shivani; Nijhawan, Tanisha; Agarwal, Varsha; *, SehbaKhatun; Parveen, Shana (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Gesture means a image of part of body. Gesture/posture Recognition is the technology that recognize the posture of body. It recognizes hand, arms, head or any part of the body. So the goal of Gesture Recognition is to provide interface of human body with computer via mathematical algorithm. This paper gives a real time vision based method for recognizing human body image using MATLAB.A number of hardware techniques are used for gathering information about body positioning; typically either image-based (using cameras, moving lights etc) or device-based (using instrumented gloves, position trackers etc.), although hybrids are beginning to come about. However, getting the data is only the first step. The second step, that of recognizing the sign or gesture once it has been captured is much more challenging, especially in a continuous stream. In fact currently, this is the focus of the paper.